Implementasi Website sebagai Media Promosi Yoyo Toys Java Mall Semarang - Supriyanto, Teguh; Ismail, Harries Arizonia; Prakoso, Satrio Agung (IAI Nasional Laa Roiba Bogor, 2025)
The rapid development of information technology has encouraged businesses to utilize digital media as an effective promotional tool. Yoyo Toys, a toy store located in Java Mall Semarang, requires a website-based promotional medium to increase its reach and facilitate customer access to information about its products and services. This study aims to design and build an interactive, informative, and responsive promotional website for Yoyo Toys. The methods used in designing this website include data collection through observation, interviews, and literature review, followed by a design process using an appropriate User Interface and User Experience approach. The final result of this study is a promotional website that can help Yoyo Toys strengthen its branding, expand its market, and provide easy online access to information for customers.